Demodulador BPSK completamente digital com portadora suprimida para telecomando de satélites - Figueredo, Caio Gomes de (2015)
This work presents a new structure for an all-digital BPSK demodulator developed for space communications that performs simultaneously the sampling and down-conversion of the the intermediate frequency signal to the baseband signal. The most important aspect of this work is the design of a new interpolator to retrieve lost samples during the down conversion process, and also to simplify the demodulator implementation. This interpolator correlates the samples of the output signal in such way that it was necessary to design a optimum filter appropriate to process the samples corrupted by gaussian and colored noise. The effects of the new interpolation at the noise are analyzed as well as the way it affects the whole demodulator performance. After performing the optimum filtering, the phase and symbol offsets are estimated and corrected. For the phase, for example, it was used a DPLL (Digital Phase Locked Loop), a digital variation of the PLL, a well known structure and largely utilized in analogical electronics. The DPLL is a closed-loop structure that estimates and corrects the values for the angular which corresponds to the phase deviation caused by the offset between the transmitter and receiver oscilators. For the timing parameter estimation, it was used the Oerder&Meyer estimator that is the digital equivalent to the well known square timing recovery structure. After that, the correction is performed by an interpolation operation over the samples of the received signal, where a filter, named Farrow filter, is applied to these samples, calculating the new samples of that signal at the corrected time instants. This system is mathematically described, all the signals expressions of every stage of the demodulator are analyzed, including the noise statistics. Some computational simulation results are shown and the performance degradation is discussed.